The Position and Role of the International Criminal Court (ICC) In International Crime Resolution - Muhammad Ghozali; Cut Afra; Deddi Agusriadi; Muhammad Yusfani; Bahraini (International Journal of Law, Social Science, and Humanities, 2025)
International crimes, such as genocide and crimes against humanity, require effective law enforcement to prevent impunity and ensure justice. The International Criminal Court (ICC) was established as a permanent court to prosecute individuals responsible for such serious crimes. This study uses a qualitative approach with documentary analysis of international legal sources, ICC reports, and case studies. Data were collected through literature reviews and interviews with international law experts to gain an in-depth understanding of the functions and challenges faced by the ICC. The results show that although the ICC has an important role in upholding international justice, its effectiveness is often hampered by jurisdictional limitations, state non-compliance, and political factors. Diplomatic steps are needed to encourage more countries to ratify the Rome Statute and increase international cooperation in enforcing ICC decisions so that justice can be achieved more effectively at the global level.